[1991] Proceedings the Fifteenth Annual International Computer Software &Amp; Applications Conference
DOI: 10.1109/cmpsac.1991.170243
|View full text |Cite
|
Sign up to set email alerts
|

A software reliability growth model for test-effort management

Abstract: We develop a software reliability growth model incorporating the amount of test-effort expenditures during software testing phase. The time-dependent behavior of test-effort expenditures is described by a Weibull curve due to the flexibility. Assuming that the error detection rate to the amount of test-effort spent during the testing phase is proportional to the current error content, the model is formulated by a nonhomogeneous Poisson process. Using this model, the method of data analyses for software reliabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The likelihood function L is: m(t) is the estimated model, m k is the cumulative number of faults detected in time interval (0, t k ], and t 0 =m 0 =0. Take the logarithm of the likelihood function in Eq (19),. (20).…”
mentioning
confidence: 99%
“…The likelihood function L is: m(t) is the estimated model, m k is the cumulative number of faults detected in time interval (0, t k ], and t 0 =m 0 =0. Take the logarithm of the likelihood function in Eq (19),. (20).…”
mentioning
confidence: 99%
“…[6][7][12][13] and was a simple modification of the NHPP to obtain an S-shaped growth curve for the cumulative number of failures detected. This model's software fault detection process can be viewed as a learning process that the software testers become familiar with the testing environments and tools as time progresses, these testers' skills gradually improve and then level off as the residual faults become more difficult to uncover [1,[6][7][12][13]. Because the original S-shaped model is for the analysis of fault isolation data, i.e.…”
Section: Yamada S-shaped Model With Logistic Testing-effort Functionmentioning
confidence: 99%
“…Musa et al [2][3] and Ohba [6] showed that the effort index or the execution time is a better time domain for software reliability modeling than the calendar time because the shape of observed reliability growth curve depends strongly on the time distribution of the testing-effort. Recently, Yamada et al [10][11][12][13] and Huang et al [14][15][16] proposed a new and simple SRGM which describes the relationship among the calendar testing, the amount of testing-effort, and the number of software faults detected by testing. The test-effort index is measured by the number of CPU hours, the number of test runs, and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation